160 THE EFFECTS OF ZINC DEFICIENCY ON GLUCOSE TOLERANCE AND GLUCAGON STIMULATED INSULIN SECRETION. (10th December 2015) - Hall, A.; Kelleher, S.; Lönnerdal, B.; Philipps, A.
Abstract : Purpose: Severe zinc (Zn) deficiency has been shown to inhibit INS storage and release. We tested the hypothesis that mild and moderate, as well as severe, Zn deficiency alters glucose (GLC) homeostasis by affecting INS release, using GLC and glucagon as physiologically different INS secretogogues. Methods: Weanling rats were fed diets containing different levels of Zn: very low Zn (VLZ, ≤1 mg Zn/kg diet), low Zn (LZ, 7 mg Zn/kg diet), mildly low Zn (MLZ, 15 mg Zn/kg diet), and control (25 mg Zn/kg diet), ad libitum for 3 weeks. In anticipation of reduced food intake, an additional group was pair-fed (PF) to VLZ rats. After 3 weeks on respective diets, rats were fasted overnight (12h), then given an intraperitoneal (ip) GLC injection (2 g/kg body weight) or ip glucagon injection (200 μg/kg body weight). Plasma samples for INS and GLC were collected at baseline and at periodic time intervals after injection. Results: In the basal state, no differences in resting plasma GLC between groups were noted. INS values were significantly decreased in VLZ and PF relative to controls with MLZ and LZ having intermediate levels. Basal (Table ) INS/GLC ratios were significantly lower in all treatment groups compared to controls and were lowest in VLZ and PF. In response to ip GLC, plasma GLC levels rose similarly in all groups. INS levels remained low in VLZ and PF compared to controls (p ≤ 0.01) and the area beneath the INS curve (AUCi) was lowest in VLZ and PF rats compared to other groups. In response to ip glucagon, plasma GLC levels rose similarly in all groups while INS levels were lower in VLZ and PF rats compared to controls after 60 min (p ≤ 0.01). AUCi after glucagon was significantly lower in VLZ rats compared to LZ, MLZ and controls (p≤0.05) and lower (p=0.07) than PF. INS levels increased less in all Zn deficient groups relative to controls after glucagon as opposed to ip GLC. Conclusion: These results confirm that INS secretion is depressed by degrees of Zn deficiency that may be observed in humans. Whether the abnormality is due to Zn-induced inability to store or release INS is not known, but both mechanisms are likely to be affected.